Introduction of new organic matter indicator and improvement of management system for quality control of drinking water in Korea - Hwang, Junyeon (KDI School, 2021)
This paper aims to introduce a new organic matter indicator in order to manage water quality consistently from water resources to drinking water, and to expand the usability of water quality results in Korea's drinking water quality standards. CODMn exists as an existing indicator of organic matter, but it has not been used as a water quality indicator several decades ago in foreign countries due to measurement inaccuracy and reliability problems. Water resources sector in Korea recognized these problems about 20 years ago and changed the water quality standard to TOC (Total Organic Carbon) through continuous researches and policy implementation. However, in the water supply sector, KMnO4 consumption similar to the CODMn method is still used as an organic matter indicator in the drinking water quality standards, but various problems similar to the CODMn method may be raised. On the other hand, as TOC is being used for water treatment process management in water treatment plants, it is urgently necessary to realize the organic matter indicator of drinking water quality standards. This paper reviewed policy trends in the water resource sector, correlation with KMnO4 consumption, TOC water quality standards draft, and environmental and economic impacts. The TOC water quality standard draft was presented as 6 mg/L by comparing the water quality standards of foreign countries and calculating the KMnO4 consumption/TOC ratio of tap water in domestic water treatment plants. In the future, it is necessary to take a long-term perspective and reflect the TOC in the water quality monitoring items for drinking water and periodically monitor it and introduce an appropriate TOC water quality standard plan.
Thesis(Master) --KDI School:Master of Public Management,2021.